Satisfacción del cliente en la intermediación turística del Cantón Baños de Agua Santa - González Freire, Daniel Enrique (2019)
Baños de Agua Santa located in the Province of Tungurahua is a charming and quiet city, surrounded by green mountains and bathed by impressive waterfalls that captivate and invite tourists to enjoy all the benefits it has. Baños has infrastructure and tourist facilities to make the stay of the tourist pleasant. Through this investigation, a problem that is found in tourist intermediation is analyzed, such as customer dissatisfaction, this is based on the research carried out and with the support instruments such as the problem tree and the matrices of operationalization and consistency where It analyzes the dimensions that are immersed in the research and that also have an impact on the satisfaction of the establishments. Therefore, this research project aims to investigate in the first instance the demand, the level of customer satisfaction when acquiring a service or product and in turn analyze in tourist intermediation establishments in the canton the level of its structure of quality with the purpose of satisfying the needs of the client, and identifying what are the determining factors in the decision making process for the implementation of the customer satisfaction improvement plan. This research project is given in four chapters starting with the problem, the justification, taking into account the objectives and hypotheses; chapter two is the theoretical framework where there are investigations with bibliographic material; The third chapter develops the methodology, this being a documentary, field investigation with the quantitative, descriptive method that applied the instruments with the lickert scale are processed in SPSS / Excel and the results are analyzed in chapter four. In the proposal we will find the possible solution for customer dissatisfaction, such as a plan to improve customer satisfaction in tourism intermediation, which in turn has a program generated and four projects aimed at the hypotheses and objectives of the research